Penanaman Pohon Sebagai Upaya Penghijauan Lingkungan Rt 13 Rw 05 Kelurahan Betungan - Ariska Antoni; Dwi Septian; Reza Afrio Utama; Rizki bunga ameli; Robby Syaputra; Siti Hanila; Leni Natalia; Khairil Khairil (Utami Publisher, 2026)
The environment plays a vital role in supporting the quality of life. However, uncontrolled development and human activities have led to a reduction in green open spaces and a decline in the quality of residential environments. This situation is also felt by the community in RT 13, Betungan Village, Bengkulu City, who face limited vegetation cover and increasing environmental pressures. This community service activity aims to improve environmental quality through tree planting as a greening effort while simultaneously raising public awareness of the importance of environmental conservation. The activity implementation method is carried out through several stages, namely identifying environmental problems, activity planning, implementing tree planting through mutual cooperation, and maintenance and evaluation. The planting activity actively involved the community service team and the local community. The results of the activity showed that all tree seedlings were successfully planted and received a positive response from residents. Community participation was evident in direct involvement in the activity and commitment to sustainable plant care. Overall, this activity has had a positive impact on increasing green cover, creating a more beautiful environment, and increasing public awareness and concern for environmental conservation.